1989
DOI: 10.1037/1040-3590.1.3.224
|View full text |Cite
|
Sign up to set email alerts
|

Assessing children's competence: Mothers' and teachers' ratings of competent behavior.

Abstract: The purposes of this study were to test the replicability of the factor structure of the Health Resources Inventory (HRI) for teachers, to describe the factor organization of the HRI when used with parents, and to assess the strength of agreement between parents' and teachers' views of children's competence. Parents' ratings were available for 269 children (ages 4 to 12 years), and teachers' ratings were gathered for a subset of 102. Analysis of teachers' responses confirmed a 5-factor structure of the HRI. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
2
11
0
1
Order By: Relevance
“…This suggests that young people who have been excluded from mainstream education are a high-risk group for mental health problems. The ndings of this study replicate the previously established high rates of behavioural problems in children with special needs (Keogh, Junoven and Bernheimer, 1989). Offord et al (1987) also showed that these rates are higher in this group of children than in the general population.…”
Section: Discussionsupporting
confidence: 89%
“…This suggests that young people who have been excluded from mainstream education are a high-risk group for mental health problems. The ndings of this study replicate the previously established high rates of behavioural problems in children with special needs (Keogh, Junoven and Bernheimer, 1989). Offord et al (1987) also showed that these rates are higher in this group of children than in the general population.…”
Section: Discussionsupporting
confidence: 89%
“…A fair amount of research regarding parent-teacher agreement on child behavior and cognitive functioning has been conducted to date (e.g., Achenbach et al, 1987;Ferdinand et al, 2003;Hundert, Morrison, Mahoney, Mundy, & Vernon, 1997;Keogh & Bernheimer, 1998;Keogh, Juvonen, & Bernheimer, 1989;Winsler & Wallace, 2002). Researchers have examined agreement on competence (Keogh et al, 1989;La Paro & Pianta, 2000;Peet, Powell, & O'Donnel, 1997), temperament (Victor, Halverson, & Smith-Wampler, 1988), and psychopathology (Ferdinand et al, 2003;Kumpulainen et al, 1999).…”
Section: Parent-teacher Agreementmentioning
confidence: 99%
“…The latter subscale contains items related to children's ability to cope with failure and other stressful situations in the school setting. It has excellent internal consistency (.88-.96; Keogh et al, 1989). The Frustration Tolerance subscale correlates negatively to externalizing problems and positively to school competence as reported by teachers and parents (Cohen et al, 1988).…”
Section: Methodsmentioning
confidence: 99%
“…The Health Resources Inventory was developed to assess specific competencies in elementary school-age children. It has well-established psychometric properties (Cohen, Kershner, & Wehrspann, 1988;Gesten, 1976;Keogh, Juvonen, & Bernheimer, 1989;Weissberg et al, 1987). Although the inventory contains a number of subscales (e.g., Academic Performance, Adaptive Assertiveness, and Peer Sociability), only the Frustration Tolerance subscale was used in the current study.…”
Section: Methodsmentioning
confidence: 99%